2023
DOI: 10.1155/2023/4131657
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Plasma: A Promising Technology for the Germination Enhancement of Radish (Raphanus sativus) and Carrot (Daucus carota sativus L.)

Abstract: Cold plasma is an innovative and promising technology that is developing in a variety of fields, and recently it has been getting a lot of attention in the agricultural industry. The influence of cold atmospheric pressure plasma (CAPP) exposure on germination parameters and vigor of radish (Raphanus sativus) and carrot (Daucus carota sativus L.) seeds was investigated in the present study. A custom-designed plasma driver utilizing 11.32 kV rms and 50 Hz was used for the generation of the discharge. Seeds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The chargevoltage (Q-V) loop is commonly known as the Lissajous figure. The power dissipated, average electron density, etc., parameters can be found from Lissajous figures as a function of several parameters [20,21]. The energy consumed per cycle is given by [22]:…”
Section: Electrical Diagnosticsmentioning
confidence: 99%
“…The chargevoltage (Q-V) loop is commonly known as the Lissajous figure. The power dissipated, average electron density, etc., parameters can be found from Lissajous figures as a function of several parameters [20,21]. The energy consumed per cycle is given by [22]:…”
Section: Electrical Diagnosticsmentioning
confidence: 99%
“…However, the data are still limited, and further research is needed to comprehensively understand the mechanisms underlying the impact of plasma on crops. Numerous research studies have been conducted in the field of plasma agriculture, with a primary focus on investigating the effects of plasma treatment on seed germination in various common and exotic crops. A model plant, Arabidopsis thaliana, has also become a subject of interest in recent plasma agriculture research. Recent studies have indicated that atmospheric plasma treatment can have a positive impact on alleviating seed dormancy in A.…”
Section: Introductionmentioning
confidence: 99%
“…It is a waterless, chemical-free, eco-friendly method with minimum food contact and higher rates of toxin destruction [10][11]. The technology of seed treatment with plasma before planting may minimize pesticide consumption during the crop cycle and increase crop yield [12].Boliu, et al,investigated the effect of plasma on the germination of eight types of seeds directly (exposingwater to plasma) and indirectly (exposing water to plasma and then placing the seeds in plasma-applied water). Their results indicated that direct plasma application is more effective on seed germination than the indirect method because of the greater impact of short-lived species produced in the direct process [1].…”
Section: Introductionmentioning
confidence: 99%
“…The etching effect of plasma on the seed tissue leads to this improvement through the water absorption capacity accession and activation of the effective physiological response [13].Cold plasma treatment increased the germination of canola seeds under drought stress [14]. The germination characteristics of radish seeds were improved by the effect of plasma for the appropriate treatment time, while the long treatment led to a decrease in the germination percentage [12]. Maxim Bafoil et al investigated the effects of lowtemperature plasma treatment on A.thaliana seed germination under salt stress and they found out that plasma application increases the germination rate of treated seeds in saline stress, which makes it possible to invest more areas with saline soil [15].…”
Section: Introductionmentioning
confidence: 99%